Optical Properties of GaAs Nanowires with an Electric Potential That Varies Inversely with the Square of the Radial Distance - Moletlanyi Tshipa (Advances in Condensed Matter Physics)
A theoretical investigation of optical properties of a cylindrical quantum wire (CQW) is presented. The properties studied were optical absorption coefficient (AC) and change in refractive index (CRI) of the quantum wire. In particular, effect of an inverse parabolic potential on the optical properties of CQWs was investigated. This was done by solving the Schrödinger equation within the effective mass approximation to obtain the wave functions. The inverse parabolic potential reduces transition energies and therefore redshifts peaks of the AC, as well as the anomalous dispersion region of the dependence of change in refractive index on the photon energy. The inverse parabolic potential also has effect on the magnitudes of these optical quantities, reducing the AC and enhancing the CRI. These properties of the inverse parabolic confining electric potential can have a wide range of applications in nanodevice technology, some details of which are discussed.